Perfuzja i krążenie pozaustrojoweECMO – a successful way to support an acutely failing heart/lungs. A chance everyone should be given - Borowicz, Marcin; Urbańska, Ewa; Przybylski, Roman; Wojarski, Jacek; Grzybowski, Adam; Szary, Tomasz; Włoczka, Grzegorz; Skalski, Janusz H.; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Extracorporeal membrane oxygenation (ECMO) is the foundation of cardiopulmonary support in infants, children and adult patients. It has been used extensively in cases of acute, severe lung and heart failure, particularly in neonates with severe lung disease. The following article describes the most commonly encountered clinical scenarios when ECMO support was required and discusses its use in both neonatal and adult patients. Moreover, safeguarding tips and frequently encountered pitfalls are emphasized.